The role of cellular oxidoreductases in viral entry and virus infection-associated oxidative stress: potential therapeutic applications. (2nd January 2016) - Mathys, Leen; Balzarini, Jan
Abstract : Introduction: Cellular oxidoreductases catalyze thiol/disulfide exchange reactions in susceptible proteins and contribute to the cellular defense against oxidative stress. Oxidoreductases and oxidative stress are also involved in viral infections. In this overview, different aspects of the role of cellular oxidoreductases and oxidative stress during viral infections are discussed from a chemotherapeutic viewpoint. Areas covered: Entry of enveloped viruses into their target cells is triggered by the interaction of viral envelope glycoproteins with cellular (co)receptor(s) and depends on obligatory conformational changes in these viral envelope glycoproteins and/or cellular receptors. For some viruses, these conformational changes are mediated by cell surface-associated cellular oxidoreductases, which mediate disulfide bridge reductions in viral envelope glycoprotein(s). Therefore, targeting these oxidoreductases using oxidoreductase inhibitors might yield an interesting strategy to block viral entry of these viruses. Furthermore, since viral infections are often associated with systemic oxidative stress, contributing to disease progression, the enhancement of the cellular antioxidant defense systems might have potential as an adjuvant antiviral strategy, slowing down disease progression. Expert opinion: Promising antiviral data were obtained for both strategies. However, potential pitfalls have also been identified for these strategies, indicating that it is important to carefully assess the benefits versus risks of these antiviral strategies.